Clinical Application Evaluation of Two Fourth‐Generation Human Immunodeficiency Virus (HIV) Screening Assays in West China Hospital. Issue 2 (5th May 2014) - Liu, Yongming; Li, Dongdong; Wang, Tingting; Yan, Kening; Zhu, Siyuan; Yang, Tingfu; Luo, Lan; Tao, Chuanmin
<x xml:space="preserve">Abstract</x> Background Fourth‐generation human immunodeficiency virus (HIV) screening assays have been used in many laboratories. The Elecsys® HIV combi PT assay is a new kind of fourth‐generation HIV screening assay developed to allow earlier detection of seroconversion. Methods A total of 271, 845 routine specimens were detected using the Elecsys® HIV combi assay and Elecsys® HIV combi PT assay from September 2010 to December 2012 in a large university hospital. Repeatedly, reactive screening samples were confirmed according to recommended confirmatory algorithms. Results The false‐positive rate and positive predictive value (PPV) of two assays are 0.08 and 78.35%, respectively, for the Elecsys® HIV combi assay and 0.07 and 82.21% for the Elecsys® HIV combi PT assay. Ninety‐four percent cases with cutoff index ratio <15.0 were false‐positive. When we set the specificity as 95.0 and 99.0%, PPV could increase to 98.7, 99.6, 98.8, and 99.7%, and sensitivity reduced to 99.2, 98.4, 98.5, and 96.8% for the Elecsys® HIV combi assay and the Elecsys® HIV combi PT assay, respectively. Conclusions The Elecsys® HIV combi PT assay shows a better performance in specificity than the Elecsys® HIV combi assay. Most weakly reactive results were false‐positive, this means it still need to be improved and it will need laboratory personnel to communicate with the clinical doctor and patients more properly about the result of the assay.